Relation entre Ptéridophytes épiphytes et leurs phorophytes en zone de montagne du rift albertin : cas du Parc national de Kahuzi-Biega en RD Congo - Bienfait Birindwa; Alfred Cubaka; Legrand Cirimwami; Roger Katusi; Jean De Dieu Mangambu (VertigO)
The present work concern the distribution of epiphytic Pteridophytes and their relationship with phorophytes in the mountain zone of the Kahuzi-Biega National Park (KBNP) in the east of the Democratic Republic of Congo (DRC). We conducted 10 transects and 20 plots on an altitudinal gradient from 1712 to 3326 meters of altitude. The inventories were made following the pattern of epiphyte distribution on phorophytes according to the method of Johansson (1974). The smallest area necessary for most species to be represented in the survey was 200 centimeters around the trunk of the phorophyte. Pteridophyte diversity indices were measured as well as the relationships between floristic variation of pteridophytes and ecological variation using principal component analysis (PCA). The 63 epiphytic Pteridophytes were recorded out of 842 phorophytes belonging to 20 species. Hemi-epiphytes (34.9%) followed by semi-strict epiphytes (25.4%) are predominant in the montane forest (1700-2600 meters of altitude) while semi-strict epiphytes dominated in the afro-subalpine forest (17.5%). The montane forest records a large number of epiphytic Pteridophytes with a sequence of I > II > III > IV > V, while the afro-subalpine forest shows a sequence of I > II > III according to the Johansson scale. Phorophyte diameter and environmental conditions are two main factors that influence epiphyte abundance. In addition, the nature of the bark of trees has a strong influence on the relationship between Pteridophytes epiphytes and phorophytes.